Mindmelding consciousness, neuroscience, and the mind's privacy - Hirstein, William (Oxford : Oxford University Press, 2012)
In this controversial book, William Hirstein argues that it is possible for one person to directly experience the conscious states of another, by way of what he calls mindmelding. Drawing on a range of research from neuroscience, psychology, and philosophy, he presents a highly original account of consciousness.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Includes bibliographical references and index.
Keywords: Consciousness; Mind and body